Pitfalls in Prostate Cancer Magnetic Resonance Imaging - Yadav, Kuldeep; Sureka, Binit; Elhence, Poonam; Choudhary, Gautam Ram; Pandey, Himanshu (Indian Journal of Medical and Paediatric Oncology, 2021)
Image-guided prostate biopsies are changing the outlook of prostate cancer (PCa) diagnosis, with the degree of suspicion on multiparametric magnetic resonance imaging (mp-MRI) being a strong predictor of targeted biopsy outcome. It is important not only to detect these suspicious lesions but also to be aware of the potential pitfalls in mp-MRI prostate imaging. The aim of this pictorial essay is to show a wide spectrum of representative cases, which are frequently misdiagnosed as PIRADS ⅘ while reporting mp-MRI of the prostate. We provide some valuable recommendations to avoid these fallacies and improve mp-MRI of prostate evaluation.
Keywords: Cancer; magnetic resonance imaging; pitfall; prostate